Exploring the Gaps, Barriers and Challenges to the Implementation of Interventions for Child Survivors of Intimate Femicide: A Case Study (Asian Journal of Social Science Studies, 2022)
Background: This paper is a product of a Dissertation submitted in partial fulfilment of the requirements for the award of a master’s degree in Social Work in 2017. The main objective of the study was to explore the gaps, barriers and challenges to the implementation of interventions for child survivors of intimate femicide (IF) in Mochudi, Botswana. Methods: The study utilized a qualitative exploratory design. In-depth interviews were conducted among 15 service providers that provide services to child survivors of IF. Thematic content analysis was employed to analyse the data. Findings: This study found that there were no interventions currently being implemented that specifically addresses the needs of the child survivors of intimate femicide. A number of challenges were identified, including; (i) service providers lack of knowledge, skills and competencies to provide services to child survivors of IF, shortage of referral systems, lack of knowledge on the existence of a network of services that exist in the community (iii) lack of collaboration and coordinated efforts by the service providers (iv) inadequate professionalised services offered to child survivors by different organisations. Conclusions and recommendations: That the “best interest of the child” be the guiding principle in provision of services to child survivors. That service providers receive professional training, parental support and coordination of services be promoted to assist child survivors.